Peningkatan Kreativitas dan Kesadaran Lingkungan melalui Proses Pembuatan Tote Bag Ecoprint: Increasing Creativity and Environmental Awareness through the Process of Making Ecoprint Tote Bags - Ariska, Karin; Fernandilla, Dea; Novianingrum, Safira Amanda (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
This community service program is entitled "Increasing Creativity and Environmental Awareness Through the Process of Making Ecoprint Tote Bags in Elementary Schools". This program aims to increase student creativity and environmental awareness through making ecoprint tote bags using natural materials. With this activity, students are expected to develop creative and innovative thinking skills and understand the importance of protecting the environment through the wise use of natural resources. The targets of this program are students at SD 3 Merbau Mataram, who are directly involved in the process of making ecoprints, starting from the selection of patterns, arrangement of leaves and flowers, to coloring techniques. The methods used include education about ecoprint, demonstration of techniques, and hands-on practice sessions. The results of this service showed a significant increase in student creativity, shown by various unique designs on ecoprinted tote bags. In addition, students are also more aware of the importance of using natural materials, which contributes to the formation of environmental care behavior. To ensure the sustainability of this program, further training and collaboration with schools and local communities are recommended. This program can be a model to increase creativity and environmental awareness in other schools.